Clinical outcomes and prognostic factors in recurrent and/or metastatic head and neck cancer patients treated with chemotherapy plus cetuximab as first-line therapy in a real-world setting. (July 2019) - Depenni, Roberta; Cossu Rocca, Maria; Ferrari, Daris; Azzarello, Giuseppe; Baldessari, Cinzia; Alù, Massimiliano; Nolé, Franco; Codecà, Carla; Boscolo, Giorgia; Piccininni, Marco; Cavalieri, Stefano; Bossi, Paolo
Abstract: Aim: The aims of the study are to evaluate the clinical outcomes of first-line treatment with platinum-based chemotherapy and cetuximab in patients with relapsing/metastatic head and neck cancer (RM HNC) and to identify predictors of treatment response. Methods: This is a retrospective, observational, longitudinal, real-world study involving 6 oncology centres in Italy. All consecutive patients with RM HNC treated between January 2007 and December 2016 with a first-line therapy consisting of a platinum-based chemotherapy regimen plus cetuximab were included. The primary objective of the study was to assess overall survival (OS) and progression-free survival (PFS). Secondary objectives included the identification of predictors of treatment response. Results: Overall, 297 patients were identified. Median OS was 10.8 months (95% confidence interval [CI] 9.3–12.2), whereas median PFS was 4.8 months (95% CI 4.3–5.5). On multivariable analysis, independent unfavourable prognostic factors for OS were performance status (PS) Eastern Cooperative Oncology Group (ECOG) >0, presence of residual tumour at primary site, platinum resistance and lack of objective response. Unfavourable predictors for PFS included cancer primary site (paranasal sinuses, hypopharynx), PS ECOG >0, presence of residual tumour at primary site, platinum resistance and lack of objective response. Independent unfavourable predictors of objective response were tumour site (oral cavity, larynx-hypopharynx), residual tumour at primary site and prior chemotherapy. Conclusions: The availability of new treatment modalities and epidemiological changes make the periodic reassessment of prognostic factors of great relevance to guide clinical practice and the design of future randomised clinical trials. Highlights: Changes in epidemiology and treatment of relapsing/metastatic head and neck cancer (RM HNC) require a reassessment of prognostic factors. Platinum resistance emerged as an important predictor of shorter progression-free survival and overall survival. Poor performance status, residual tumour at primary site and no objective response play a prognostic role. After the adoption of the EXTREME regimen for RM HNC, prognostic factors profile has changed.